OPPORTUNITIES AND CHALLENGES FOR INTEGRATIVE CURRICULUM DEVELOPMENT IN MADRASAH TSANAWIYAH - Welsi Damayanti; Rohayati; H. Suhada (Adisam Publisher, 2024)
The role of Islamic education among Muslims as the religion of the majority of Indonesia's population is a manifestation of the ideals of Islamic life to preserve, transfer, instill and transform Islamic values to future generations. The madrasa grows and develops based on the responsibility to convey Islamic teachings to the next generation. Integrative curriculum development requires strategic and comprehensive planning, referring to laws and government regulations that regulate the implementation of higher education. Curriculum preparation needs to pay attention to national insight, international quality, local potential, and collective intelligence among teachers. Developing an integrative curriculum is both a challenge and an opportunity for schools to be able to provide educational services that are in line with current developments. Thus, Madrasah Tsanawiyah must have sufficient competence in developing a curriculum at the Islamic education level. This development can take the form of material content that is enriched by scientific treasures or learning methods that are relevant to the course material being taught, so that the quality of education in Indonesia becomes high quality.